THE PREVALENCE, ISOLATION, AND ANTIMICROBIAL SUSCEPTIBILITY TESTING OF ENTEROCOCCUS SPECIES FROM VARIOUS CLINICAL SAMPLES IN A TERTIARY CARE HOSPITAL - Afroz, Turin (Journal of Vocational Health Studies, 2024)
Background: Enterococcus is routinely considered a low-grade pathogen. The synergistic action of Enterococci with other bacteria increases the risk of infection. Enterococci are currently the next most common cause of healthcare-associated infections after E. coli. Greater understanding is needed regarding Enterococcus stress survival, virulence, and resistance patterns to assess the complexity of disease-causing Enterococcus. Purpose: Analyze the prevalence of Enterococcus and assess the antibiotic sensitivity pattern of Enterococcus. Method: A descriptive cross-sectional study was designed and carried out in the Department of Microbiology at Bangladesh University of Health Sciences, Dhaka, over a period of 3 months. Bacterial culture and sensitivity were the methods employed for microbiological examination. Result: A total of 558 bacterial strains were isolated, among which the growth of Enterococcus spp. was 27 (4.83%). The prevalence of Enterococcus spp. among different samples was 4.83%. The number of highly sensitive strains ranged from 66.66% to 77.77% for antibiotics, namely gentamycin, ampicillin, amoxicillin, and meropenem. Moderately high sensitivity to levofloxacin (29.62%) and low sensitivity to doxycycline (14.81%) were also analyzed. Conclusion: The study recommends that antibiotics should be used after proper laboratory procedures are undertake, and it should be selected based on antimicrobial susceptibility tests.